Muscle changes during direct attack under different conditions in elite wheelchair fencing - Martín-Ruiz, J.; Alarcón-Jiménez, J.; de Bernardo, N.; Tamarit-Grancha, I.; Iglesias, X.; Ruiz-Sanchis, L. (Sports, 2024)
Wheelchair fencing is a medium-distance combat sport in which the wheelchair is fixed to the floor. This requires a maximum concentration and gestational speed. Refined techniques and fatigue tolerance are essential to achieve competitive results. Aim: The main objective of this study was to measure the speed and muscular participation of a direct attack gesture with and without fatigue in a sample of elite wheelchair fencers. Methods: The maximal isometric force, gestural speed, and resistance to gestural velocity were estimated in 10 elite performed direct fencers. Results: The results revealed that sitting height and wingspan were important factors in achieving the highest speed, especially in women (r = 0.9; p = 0.07). Other factors, such as the elbow angle where the closed position was better, affected muscle contraction in both categories of athletes (p = 0.01). The onset of fatigue was earlier in category B than in category A, with greater variation in direct attack movement. The results highlight the importance of analyzing direct attacks for the best application of quick force, speed, and muscle participation, as well as identifying the onset of technical deterioration to devise a competitive strategy. These parameters may allow for precise design of conditioning sessions for elite wheelchair shooters.